2009
DOI: 10.1089/pop.2009.0007
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Retail Medicine on Standard Costs in Primary Care: A Semiparametric Analysis

Abstract: Retail medicine clinics have become widely available. However, few studies have been published that compare retail clinic costs of care to standard medical visits for similar patients. The purpose of this study was to compare standard medical costs during a 6-month period after visiting a retail medical clinic to care received in a conventional medical office setting. Medical records of primary care patients (both adults and children) seen in a large group practice in Minnesota in 2008 were analyzed for this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 7 publications
(7 reference statements)
0
14
0
Order By: Relevance
“…Charges for minor illnesses treated are often less than a physician office and much less than an emergency department. 11,12 Many RBCs bill insurance carriers, and some are able to bill Medicaid. 8 Data on outcomes specifically looking at pediatric patients are limited, but minor illnesses, such as acute pharyngitis, demonstrate no significant issues with early return visits to primary care physicians.…”
Section: Growth Acceptance and Direction Of Rbcsmentioning
confidence: 99%
See 1 more Smart Citation
“…Charges for minor illnesses treated are often less than a physician office and much less than an emergency department. 11,12 Many RBCs bill insurance carriers, and some are able to bill Medicaid. 8 Data on outcomes specifically looking at pediatric patients are limited, but minor illnesses, such as acute pharyngitis, demonstrate no significant issues with early return visits to primary care physicians.…”
Section: Growth Acceptance and Direction Of Rbcsmentioning
confidence: 99%
“…8 Data on outcomes specifically looking at pediatric patients are limited, but minor illnesses, such as acute pharyngitis, demonstrate no significant issues with early return visits to primary care physicians. 7,12,13 RBCs are located in retail stores, such as grocery stores, drug stores, or "big box" stores. Average driving time for patients is less than 5 minutes, and average income and education for communities with RBCs are above average nationwide.…”
Section: Growth Acceptance and Direction Of Rbcsmentioning
confidence: 99%
“…Earlier studies of outpatient clinical care have suggested a strong association between increased use of resources before an intervention and the amount of use after an intervention. As such, to fully appreciate the impact on an individual patient's use, prior use should be controlled . High utilizers may already have additional resources, such as general care managers, that control potential future utilization.…”
Section: Discussionmentioning
confidence: 99%
“…20,21,22,23 Finally, recent studies of RCs have found that they also engage in cream skimming the less severely ill patients but deliver less costly care, controlling for severity. 24,25 There is some evidence regarding quality standards practiced in such clinics and comparable levels of quality of care relative to physician offices. 11,14,26,27 However, the clinics seem to attract patients lacking a primary care physician, suggesting they may serve as more of a safety net provider than a disrupter.…”
Section: Radical and Disruptive Elements That Challenge Incumbentsmentioning
confidence: 99%